Prediction and Correlations of Residual Entropy of Superheated Vapor for Pure Compounds - O. Abdullah, Mahmoud; T. Najim, Sarmad; Z. Atta, Shahad (Iraqi Journal of Chemical and Petroleum Engineering, 2012)
Prediction of accurate values of residual entropy (SR) is necessary step for the calculation of the entropy. In this paper, different equations of state were tested for the available 2791 experimental data points of 20 pure superheated vapor compounds (14 pure nonpolar compounds + 6 pure polar compounds). The Average Absolute Deviation (AAD) for SR of 2791 experimental data points of the all 20 pure compounds (nonpolar and polar) when using equations of Lee-Kesler, Peng- Robinson, Virial truncated to second and to third terms, and Soave-Redlich-Kwong were 4.0591, 4.5849, 4.9686, 5.0350, and 4.3084 J/mol.K respectively. It was found from these results that the Lee-Kesler equation was the best (more accurate) one compared with the others, but this equation is sometimes not very preferable. It was noted that SRK equation was the closest one in its accuracy to that of the Lee-Kesler equation in calculating the residual entropy SR of superheated vapor, but it was developed primarily for calculating vapor-liquid equilibrium and to overcome this problem, efforts were directed toward the possibility of modifying SRK equation to increase its accuracy in predicting the residual entropy as much as possible. The modification was made by redefining the parameter α in SRK equation to be a function of reduced pressure, acentric factor, and polarity factor for polar compounds in addition to be originally function of reduced temperature and n parameter –which is also function of acentric factor– by using statistical methods. This correlation is as follows: α =[1+n(γ)]2 , γ=-0.920338Pr-0.34091 +0.064049Tr4 ω +0.370002ω-Pr0.996932 Tr-4x This new modified correlation decreases the deviations in the results obtained by using SRK equation in calculating SR when comparing with the experimental data. The AAD for 2791 experimental data points of 20 pure compounds is 4.3084 J/mol.K while it becomes 2.4621 J/mol.K after modification. Thus SRK equation after this modification gives more accurate results for residual entropy of superheated vapor of pure 20 compounds than the rest of the equations mentioned above.